Atopy as a risk factor for thyroid autoimmunity in children affected with atopic dermatitis. (3rd October 2013) - Pedullá, M.; Fierro, V.; Papacciuolo, V.; Alfano, R.; Ruocco, E.
Abstract Background As a result of several clinical reports addressing coincidence or coprevalence of atopy and autoimmune disease such as multiple sclerosis and type I diabetes mellitus, there has been considerable interest in defining the relationship between the expression of allergic and autoimmune disease in populations of patients. Although thyroid autoimmunity has been regularly associated with chronic urticaria in children, the cofrequency of thyroid autoimmunity and atopic dermatitis has not yet been investigated. The aim of the study was to describe our experience with children affected by atopic dermatitis and associated thyroid autoimmunity. Methods From January 2010 to December 2012, 147 children affected by atopic dermatitis were consecutively referred to the Pediatric Clinic of the Pediatric Department at the Second University of Naples. Seventy healthy children of comparable ages, unaffected by atopic dermatitis, atopy or thyroid disease, served as a control group. Results On the basis of skin prick test results we selected 54 IgE‐mediated (36.7%) and 93 non‐IgE‐mediated AD (63.3%) children. Fourteen of 147 patients (9.52%) showed increased levels of antithyroid antibodies. Conclusions Our results therefore suggest that atopy, especially food allergy, and autoimmunity are two potential outcomes of dysregulated immunity.